Analisis Strategi Pengembangan Sumber Daya Insani (Sdi) Dalam Meningkatkan Kinerja Karyawan Pada Lazismu Kota Medan - Odylia Azhura Warman (CERED Indonesia Institute, 2022)
The purpose of the research studied is to find out what training systems are carried out in Lazismu Medan City, To find out monitoring of employee performance appraisals at Lazismu Medan City, To find out factors supporting and inhibiting performance at Lazismu Medan City, To determine Employee Performance Development Strategies at Lazismu City Medan. Research Methods This thesis is a type of qualitative research, data collection techniques using interviews / interviews, namely direct question and answer dialogue between researchers and research respondents. Documentation, which is a record of data that has been valid. Documentation is done by looking for data about matters related to research, both in written form such as books, magazines, journals, documents, reports and others as well as in the form of images. The results of this study indicate that the development of human resources is the main point that must be emphasized in the company, either individually or by employees or as a group, which is very much needed by the company.